Diet proposition based on the food pyramid for patients with chronic obstructive pulmonary disease - Alberto Soares da Costa, Carlos; Souza de Oliveira Sampaio, Gabriel (Cadernos de Ensino e Pesquisa em Saúde, 2022)
The aim was to develop a diet proposal, based on a review of the literature on food pyramids for individuals with Chronic Obstructive Pulmonary Disease (COPD), in order to be used in diet therapy applied to adult men and women with COPD. Food pyramids are important tools used for food and nutrition education purposes. Previously, Rondanelli et al. (2020) developed an adapted food pyramid, along with guidelines for energy and dietary intake, in order to prevent and treat nutritional complications associated with COPD, but it was not translated into dietary planning. Four different diets were herein elaborated, two of them comprised 50% lipids and 30% carbohydrates and the other two comprised 50% carbohydrates and 30% lipids. Data on the mean body weight of men and women in the age group 35-44 years, as well as recommendations for food pyramid macro and micronutrients, were taken into account to build the dietary plan. Four food composition tables were used to select the food types forming the meal plan. The herein proposed diets have anti-inflammatory and antioxidant properties; this factor required some considerations about their composition for the Brazilian context. It is essential promoting this diet therapy instrument to help professionals in the nutrition field to set a conduct more compatible to individual features of both patients and their lung disease.